Quantification of deltamethrin residues in wheat by Ag@ZnO NFs-based surface-enhanced Raman spectroscopy coupling chemometric models. (1st February 2021) - Jiao, Tianhui; Mehedi Hassan, Md; Zhu, Jiaji; Ali, Shujat; Ahmad, Waqas; Wang, Jingjing; Lv, Changxin; Chen, Quansheng; Li, Huanhuan
Graphical abstract: Highlights: The rapid quantification of deltamethrin in wheat was described. The Ag@ZnO NFs SERS substrate was obtained for deltamethrin quantification. Chemometric models were used for spectral mining and predictive modeling. The influence of built models on detective performance was discussed. Abstract: Deltamethrin, one of the most toxic pyrethroids, is commonly used to inhibit pests in wheat. However, the trace levels of deltamethrin in wheat is alarming to human health. In this study, surface-enhanced Raman spectroscopy (SERS)-active silver nanoparticles-plated-zinc oxide nanoflowers (Ag@ZnO NFs) nano-sensor were employed for rapid and sensitive quantification of deltamethrin in wheat. To sufficiently utilize the chemical-related information in SERS spectra, various spectral pretreatment and chemometric models were studied. The mean centering (MC) coupling successive projection algorithm-partial least squares regression (SPA-PLS) provided optimal predictive performance (correlation coefficient of prediction (Rp) = 0.9736 and residual predictive deviation (RPD) = 4.75). The proposed method achieved the limit of detection (LOD) = 0.16 μg·kg −1, the recovery of predicted results was in the range of 96.33–109.17% and the relative standard deviation (RSD) was < 5%. The overall results suggested that SERS based Ag@ZnO NFs combined with MC-SPA-PLS could be an easy and efficient method to quantify deltamethrin residue levels in wheat.